2021
DOI: 10.1542/hpeds.2021-006060
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound Training in Pediatric Residency: A National Needs Assessment

Abstract: BACKGROUND AND OBJECTIVES As point-of-care ultrasound (POCUS) evolves into a standard tool for the care of children, pediatric residency programs need to develop POCUS training programs. Few POCUS training resources exist for pediatric residents, and little is known about POCUS training in pediatric residencies. We aim to describe pediatric residency leadership perspectives regarding the value of POCUS and to elucidate the current state of POCUS training in pediatric residency programs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…This study was able to demonstrate that our novel POCUS curriculum led to knowledge acquisition and improved confidence in pediatric trainees. There is a clear demand for POCUS education of pediatric residents, from both the perspective of program leadership and trainees, who recognize the importance of this skill and who desire POCUS training 19 , 20 , 21 . We suggest that our novel curriculum combining QB and in-person learning could serve this demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was able to demonstrate that our novel POCUS curriculum led to knowledge acquisition and improved confidence in pediatric trainees. There is a clear demand for POCUS education of pediatric residents, from both the perspective of program leadership and trainees, who recognize the importance of this skill and who desire POCUS training 19 , 20 , 21 . We suggest that our novel curriculum combining QB and in-person learning could serve this demand.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate survey, pediatrics residents overwhelmingly felt that POCUS training should be required during residency, yet only 15% of respondents had received such training 19 . A national survey of pediatric residency associate program directors showed that a majority of respondents felt that POCUS should be taught to their trainees 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound (US) training is required by the Accreditation Council for Graduate Medical Education (ACGME) for residents in EM, family medicine, and anesthesiology 3–5 . Many large specialties, including internal medicine, pediatrics, obstetrics and gynecology, and surgery, have also advocated for integrated US curricula to improve resident competency 6–9 . When implementing US training at all levels of medical education, a variety of training methods are utilized, including hands‐on experiential learning.…”
Section: Introductionmentioning
confidence: 99%
“…In repeated surveys about providing POCUS training, lack of local expertise and resources are almost universally cited barriers to beginning and/or sustaining a POCUS training program. [6][7][8][9][10] Utilizing national programs, such as the American College of Surgeons' Ultrasound Essentials for Surgeons Course or the American College of Chest Physicians' Critical Care Ultrasound Course, allows GME trainees to nd extra-curricular opportunities for POCUS training during residency or fellowship. However, these courses are limited by their high cost and the time needed to travel for already busy GME trainees.…”
Section: Introductionmentioning
confidence: 99%